KOMORBIDITAS PADA EPISODE REKUREN SINDROM POSNER-SCHLOSSMAN DAN NEUROPATI OPTIK KARENA ETAMBUTOL - Angela Shinta Dewi Amita; Kristian Dernitra; Thendy Foraldy (Atma Jaya Catholic University of Indonesia, 2020)
Introduction: Posner-Schlossman Syndrome (PSS) or glaucomatocyclitic crisis is a rare ophthalmic disease characterized by unilateral, acute, and recurrent attacks of elevated intraocular pressure (IOP) accompanied by mild anterior chamber inflammation without any conclusive causative factor. This case report represents a concurrence of Ethambutol-induced Optic Neuropathy (EON) and recurrent episode of PSS. Although this combination rarely occurs, but it can significantly affect the prognosis of both conditions.Case: A 41-year-old woman with unilateral ocular pain and blurred vision for the last 24 hours presented with left anterior uveitis, elevated intraocular pressure 56.7 mmHg and was diagnosed with left eye PSS. Five years later she showed signs of bilateral EON after 5 months of ethambutol administration as tuberculosis treatment. Best Corrected Visual Acuity (BCVA) was (20/80 OD, 20/70 OS), with an unspecified bilateral cecocentral scotomas. After 1 month of ethambutol cessation, the patient had a recurrent episode of PSS on the left eye and worsening the visual acuity more on both eyes (20/400 OD, 20/200 OS). The patient was then treated with methylprednisolone injection, and the visual acuity starts to improve (20/100 ODS).Conclusion: Comprehensive examination to detect probable etiologies of PSS is important to prevent recurrences and possible comorbidities with other eye disease, such as EON in this case. Patients undergoing ethambutol medication should be assessed by an ophthalmologist before, during and after finished treatment to evaluate the patient’s risk factors, past medical history and progression of visual acuity during treatment.